Pupal cases of four Nearctic species of Laphria (Diptera: Asilidae) - Dennis, D. Steve; Barnes, Jeffrey K. (Zootaxa, 2013)
The pupal cases of the Nearctic robber flies Laphria canis Williston, 1883: L. ferox Williston, 1883: L. macquarti (Banks, 1917): and L. posticata Say, 1824 are described and illustrated. A key is provided to the pupal cases of these and seven other species of Laphria previously described. A revised key also is included for the pupal cases of three genera of Laphri-inae: Andrenosoma, Lampria, and Laphria. s,j vl3# t! gues and Zaher 2011 and C. venetacaudus Arias, Carvalho, Rodrigues and Zaher 2011. We analyzed the external and hemipenial morphology of specimens from different localities in the state and our re-sults indicate the presence of at least four species: C.cf. ocellifer, C. confusionibus, C. venetacaudus and C. pyrrhogularis sp. nov. Hemipenial analysis corroborates the existence of two subgroups within C. ocellifer species group. Cnemidopho-rus pyrrhogularis sp. nov., a member of the ocellifer subgroup, occurs in the northern part of Piauí, in ecotonal areas, and differs from the remaining species of the genus mainly on hemipenial morphology, number of femoral pores, number the lamellae under fourth finger and fourth toe, and color pattern. Diagnoses and hemipenis description of the four taxa are presented, as well as a detailed description of the new species.